Endogenous Local Labour Markets, Regional Aggregation and Agglomeration Economies - Jordy Meekes; Wolter Hassink (Institute of Labor Economics (IZA), 2019)
This paper examines the role of regional aggregation in measuring agglomeration externalities. Using Dutch administrative data, we define local labour markets (LLMs) based on the worker's commuting outcomes, gender and educational attainment, and show that high-educated workers and male workers are characterised by a relatively large LLM. We find that the effect of employment density on workers' wages increases in the level of regional aggregation, explained by larger agglomeration externalities at a higher spatial scale. We quantify subgroup differentials and find that high-educated workers have agglomeration externalities twice as high as low-educated workers. We show that workers who lose their job in denser LLMs experience positive agglomeration externalities on job matching, with more modest losses in wages and again larger density effects at higher levels of regional aggregation.
Keywords: R12; R23; J31; J6; 330; urban wage premium; job loss; local labour markets; commuting; agglomeration